Antibacterial properties of lucifensin in Lucilia sericata maggots after septic injury - Valachova, Ivana (Asian Pacific Tropical Medicine Press, 2014)
OBJECTIVE: To investigate the antibacterial properties of lucifensin in maggots of Lucilia sericata after septic injury. METHODS: In our preliminary study we have shown that injuring the maggots with a needle soaked in lipopolysaccharide solution induced within 24 h lucifensin expression in the fat body and in the grease coupler of the salivary glands. It is assumed that lucifensin is secreted solely from this tissue into the haemolymph (similar to other insect defensins) and not into secreted/excreted products. We used high-performance liquid chromatography fractionation and radial diffusion assay to investigate the antibacterial properties of haemolymph extracted from larvae after septic injury. RESULTS: After septic injury, production of lucifensin in the haemolymph is increased. This led to higher antibacterial activity of such haemolymph in comparison to non-stimulated larvae. COCLUSIONS: These results suggest that beside the previously demonstrated role of lucifensin in the debridement therapy, lucifensin is simultaneously important as a part of the systematic immune response.